The Influence of the EU Council Presidency on National Coordination Mechanisms for European Agenda - Johana Galušková (Romanian Journal of European Affairs)
This article examines the degree to which holding the Presidency of the Council of the EU (Presidency) influences CEE countries’ national systems of European affairs coordination. It utilizes process tracing to map out the coordination mechanisms for individual countries along three dimensions: centralization, selectivity, and coordination tools (both technical and personnel-based). Making use of the critical junctures concept, which presumes disruption of fluent institutional development, the study explores whether the Presidency may indeed be one of these disruptive moments. It points out the significance of the Presidency not only at the European level, but particularly at the national level, as well. This national-level influence comes in varying degrees, depending both upon the dimensions involved and the individual states concerned. It confirms that personnel changes are the rule, and an influence on technical tools is also frequently exhibited. But it is more exceptional for centralization and selectivity to be affected, and this was confirmed for the Czech Republic (CR), partly for Poland and Lithuania.